Regulation of autophagy by non-coding RNAs in gastric cancer - Wang, Zijian; Liu, Jiarui; Xie, Jingri; Yuan, Xingxing; Wang, Bingyu; Shen, Wenjuan; Zhang, Yang (Frontiers in Oncology, 2022)
Autophagy is a conserved cellular self-digesting process that degrades obsoleting proteins and cellular components and plays a crucial role in the tumorigenesis, metastasis, and drug resistance of various tumors such as gastric cancer (GC). As a hotspot in molecular biology, non-coding RNAs (ncRNAs) are involved in the regulation of multiple biological processes, such as autophagy. Increasing evidence indicate that various ncRNAs exert double roles in the initiation and progression of GC, either serve as oncogenes or tumor suppressors. Recent studies have shown that some ncRNAs could modulate autophagy activity in GC cells, which would affect the malignant transformation and drug resistance. Whether the function of ncRNAs in GC is dependent on autophagy is undefined. Therefore, identifying the underlying moleculr targets of ncRNAs in autophagy pathways and the role of ncRNA-regulated autophagy in GC could develop new treatment interventions for this disease. This review summarizes the autophagy process and its role in GC, and the regulatory mechanisms of ncRNAs, as well as focuses on the dual role of ncRNAs-mediated autophagy in GC, for the development of potential therapeutic strategies in GC patients.